1958
DOI: 10.1084/jem.108.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin-Induced Inhibition of the Pituitary-Adrenal Stress Response

Abstract: Glycyrrhizin decreased the resistance of intact male mice to prolonged exposure to cold (8 hours at 5°C.) and it decreased the ability of intact male rats to mobilize glucose when subjected to 48 hours of fasting. It is suggested that glycyrrhizin, like desoxycorticosterone, depresses the output of ACTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In comparison with control, ammoniated glycyrrhizin decreased survival time. Besides, it has been shown that treated rats with 0.4% ammoniated glycyrrhizin in drinking water for 1 week were more sensitive to 48‐h fasting and showed severe hypoglycemia versus control (Kraus, ). However, Finney et al .…”
Section: Toxicological Findingsmentioning
confidence: 97%
“…In comparison with control, ammoniated glycyrrhizin decreased survival time. Besides, it has been shown that treated rats with 0.4% ammoniated glycyrrhizin in drinking water for 1 week were more sensitive to 48‐h fasting and showed severe hypoglycemia versus control (Kraus, ). However, Finney et al .…”
Section: Toxicological Findingsmentioning
confidence: 97%